A new whip spider (Arachnida: Amblypygi) in mid-Cretaceous Kachin amber. (December 2020) - Hu, Xueying; Lei, Xiaojie; Luo, Cihang; Jarzembowski, E.A.; Wang, Bo; Xiao, Chuantao
Abstract: A new genus and species of fossil whip spider (Chelicerata: Amblypygi), Burmacharon dunlopi gen. et sp. nov., is described from mid-Cretaceous Kachin (Burmese) amber of Myanmar. The new genus can be distinguished from the genus Kronocharon by the anterior margin of the carapace being slightly procurved (projected forwards and slightly rounded), and the opisthosoma is rather elongate, almost twice as long as wide. Burmacharon dunlopi is the fourth species of Cretaceous amber whip spider. Our find adds some novel information to the knowledge of the morphological and taxonomic palaeodiversity of Mesozoic whip spiders.